The influence of anxiety on eating disorders (Research, Society and Development, 2023)
Anxiety is seen as the evil of the century. Eating behavior can be influenced by emotional state, a psychological state associated with excessive worry, tension and future distress, which can include symptoms of restlessness, nervousness, excessive worry, eating disorders and difficulty sleeping. The present research aimed to comprehensively investigate and analyze the interrelationship between anxiety and eating disorders, exploring the underlying psychological mechanisms, identifying triggering factors and proposing possible therapeutic approaches to mitigate the negative impacts of this complex relationship on mental health and physicality of individuals. Anxiety can play a significant role in encouraging the development of eating disorders, such as anorexia, bulimia nervosa, or binge eating disorder. The relationship between the two is complex and multifaceted. People with these disorders may use food as a way to cope with anxiety and other difficult emotions, restricting themselves from eating in stressful situations to feel in control. Others turn to food as a temporary "escape", leading to binge eating. Anxiety is also associated with body image, leading to body dissatisfaction and the search for unhealthy paths. The cycle of shame and guilt surrounding eating behavior. Several neurotransmitters are known to play an important role in controlling anxiety. Gamma-aminobutyric acid (GABA) is an inhibitory neurotransmitter in the brain which means its role is to decrease the activity of nerve cells, thus reducing neural excitation. In this study it was observed that anxiety is linked to our emotions and, when altered, leads to health problems, such as eating disorders.